Efektivitas Metode Pemberian Tugas Berbasis Corel Draw Pada Mata Pelajaran Pendidikan Agama Islam - Agus Jayadi; Zul Anwar; Misbahul Adey Yaziz (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
This research aims to determine the effectiveness of the Corel Draw-based Assignment Method in Islamic Religious Education Subjects at State Vocational High School 2 Kuripan for the 2022/2023 academic year. Giving assignments is a way of presenting material where educators give certain tasks so that students carry out learning activities individually or in groups by being accountable for their work to the teacher. The research is quantitative research with a quasi-experimental approach with a one-group-pretest-posttest design. The data collection method used in this research is a questionnaire as the main method, while observation and documentation are used as supporting or complementary methods. The data analysis technique used is N-Gain which was popularized by Sugiono. The calculation results for each variable are: the pretest score for the assignment variable was 72 and the posttest score for the assignment variable was 80. Meanwhile, the pretest score for the learning achievement variable was 73.9 and the posttest score for the learning achievement variable was 80. .6. Based on the data above, there is a significant difference between before and after using the Corel Draw-based assignment method, meaning that using the Corel Draw-based assignment method has an effect on student learning achievement.